International Laws and The Reality: The Complexity of Corporate Law in Empowering Human Rights - Sudirman, Lu; Tan, David; Tan, Winsherly; Situmeang, Ampuan (Jambura Law Review, 2024)
Corporations inevitably violate human rights in a variety of ways. As corporations evolved into massive multinational businesses, corporate violenceâ€”which is a legacy of colonialism and corporate powerâ€”continues to exist today. Corporate players maintain their freedom in pursuing their objectives using convoluted and obscure multinational organizations and supply networks, through the utilization of corporate law principles like the veil of corporate ownership, and also through other practices like tax evasion and lobbying of political bodies. The objective of this article is to explore the legal aspects of the problem of corporate violence, and suggesting reforms to ensure justice for the affected parties. This article uses the doctrinal research method along with the comparative method, focusing on both primary and secondary data. This article makes the case that the issue stems from the structural and systemic flaws in the framework of international law as well as in corporate laws that continually preserve corporate institutions in frustrating the advancement of the cause for human rights.  To effectively enhance the corporate and human rights environment, a framework of hard law, soft law, and non-law reforms and actions is needed.